Ecotypic variation and plasticity of growth, survival and ontogeny in provenances of Canary islands pine - López R.; Climent J.; Chambel M.R.; Gil L. (Proceedings of the international workshop MEDPINE 3: conservation, regeneration and restoration of Mediterranean pines and their ecosystems, 2007)
Height, survival and ontogeny (juvenile, intermediate or adult stages) were measured during the first six years after planting in a provenance trial of Pinus canariensis established in four sites in Canary Islands (Spain). We could observe an ecotypic variation pattern related to seed origin that affected survival in the less favourable sites as well as heteroblasty in the trial as a whole. Provenances from drier and warmer areas presented in general retarded ontogeny and better survival rates. Height growth showed a predominance of phenotypic plasticity (site factor) against the differentiation among provenances. In addition, total height exhibited higher variation among provenances, even neighbouring ones, than among ecological regions.
Proceedings of the International Workshop, 2005/09/26-30, Bari (Italy)